2021
DOI: 10.1021/acs.jpcc.0c08957
|View full text |Cite
|
Sign up to set email alerts
|

Design Considerations for Oligo(p-phenyleneethynylene) Organic Radicals in Molecular Junctions

Abstract: Spin polarization in the electron transmission of radicals is important for understanding single-molecule conductance experiments focusing on shot noise, Kondo properties, or magnetoresistance. We study how stable radical substituents can affect such spin polarization when attached to oligo(p-phenyleneethynylene) (OPE) backbones. We find that it is not straightforward to translate the spin density on a stable radical substituent into spin-dependent transmission for the para-connected wires under study here, ow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 148 publications
0
19
0
Order By: Relevance
“…It was noted that larger spin polarisation (and potentially enhanced Kondo features, see below) might be achieved by using meta-OPE analogues, where reduced intramolecular steric hindrance would be expected. 267 This would lead to a more coplanar backbone and hence increased spin delocalisation along the OPE wire, although as discussed in section 3.2 lower overall conductance would be expected. Incorporating radical functionality directly into the molecular backbone may not be straightforward either; a (non-OAE) molecular wire with an otherwise stable Blatter radical in its backbone appeared to oxidise to a closed-shell species when bound between electrodes in STM-BJ experiments.…”
Section: Molecular Spintronicsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was noted that larger spin polarisation (and potentially enhanced Kondo features, see below) might be achieved by using meta-OPE analogues, where reduced intramolecular steric hindrance would be expected. 267 This would lead to a more coplanar backbone and hence increased spin delocalisation along the OPE wire, although as discussed in section 3.2 lower overall conductance would be expected. Incorporating radical functionality directly into the molecular backbone may not be straightforward either; a (non-OAE) molecular wire with an otherwise stable Blatter radical in its backbone appeared to oxidise to a closed-shell species when bound between electrodes in STM-BJ experiments.…”
Section: Molecular Spintronicsmentioning
confidence: 99%
“…266 The limited spin filtering behaviour of 78 is supported by a recent computational study of other structurally similar radical-bearing OPE3s, which found that good orbital overlap between the π-systems of the OPE backbone and radical is needed to achieve appreciable spin filtering. 267 Unfortunately this is difficult to achieve experimentally as significant steric shielding, which promotes divergence from coplanarity, is usually required to stabilise organic radicals. It was noted that larger spin polarisation (and potentially enhanced Kondo features, see below) might be achieved by using meta-OPE analogues, where reduced intramolecular steric hindrance would be expected.…”
Section: Molecular Spintronicsmentioning
confidence: 99%
“…[8][9][10] In particular, the molecular conductance of organic radicals has recently started attracting interest in conjunction with their characteristic spintronic behaviors represented by magnetoresistance and the Kondo resonance. [11][12][13][14][15][16][17][18] Hayakawa, Scheer, and co-workers have observed 1.6 � 1.9-fold larger conductance of TEMPO-OPE compared with nonradical OPE at zero field in the course of investigating magnetoresistance (Figure 1) by the MCBJ method. [13] It is intriguing that the remote radical induced non-negligible enhancement.…”
Section: Introductionmentioning
confidence: 98%
“…Since the flourishing of the mechanically controllable break junction (MCBJ) and scanning tunneling microscopy‐break junction (STM‐BJ) techniques, [1,2] molecular structure‐conductance relationships have been disclosed from various viewpoints such as dihedral angle, [3,4] substituents, [5–7] and molecular orbital [8–10] . In particular, the molecular conductance of organic radicals has recently started attracting interest in conjunction with their characteristic spintronic behaviors represented by magnetoresistance and the Kondo resonance [11–18] . Hayakawa, Scheer, and co‐workers have observed 1.6±1.9‐fold larger conductance of TEMPO‐OPE compared with nonradical OPE at zero field in the course of investigating magnetoresistance (Figure 1) by the MCBJ method [13] .…”
Section: Introductionmentioning
confidence: 99%
“…16,17 More generally, radical molecular species have been identified as exceptionally promising compounds for use in the development of the field of molecular electronics. [18][19][20][21][22][23] The incorporation of a molecular system featuring an unpaired electron within an electrode | molecule | electrode junction leads to a host of fascinating electronic properties, 24 including enhanced rectification, 25 spin-gating, 26 Kondo effects, 27 magnetoresistive effects 28 and quantum interference, 29 whilst the redox-activity of such systems allows for an exciting range of electrochemically gated applications. [30][31][32][33] This has prompted exploration of a small number of perchlorotriphenylmethyl radicals 25,[34][35][36][37] as well as radical species generated within a molecular junction by in situ redox [38][39][40][41][42][43][44] or chemical 29 processes.…”
Section: Introductionmentioning
confidence: 99%